Homotypic aggregation of murine T lymphocytes induced by anti-Thy-1 monoclonal antibodies. - Isobe, K (1991)
During the course of studies of anti-Thy-1-mediated T-cell activation, we found that anti-Thy-1 monoclonal antibodies (mAb) could induce strong homotypic aggregation of murine T-lineage cells. We demonstrated that anti-Thy-1 mAb-mediated T-cell aggregation started at 10 min and reached maximum level 1 hr after addition of antibody. It was temperature dependent, requiring metabolic energy and cytoskeletal integrity similar to that mediated by phorbol myristate acetate (PMA). But the striking difference between anti-Thy-1 mAb-mediated cell aggregation and PMA-mediated cell aggregation was that the latter but not the former was blocked by anti-LFA-1 mAb. This indicates that, unlike treatment with PMA, anti-CD2 mAb or anti-CD3 mAb, anti-Thy-1 mAb treatment of T lymphocytes does not induce LFA-1 activation for cell adhesion. Murine neuroblastoma cells were not induced to aggregate by anti-Thy-1 mAb treatment, although murine T lymphoma cells were aggregated by anti-Thy-1 mAb. The T-lineage cell specificity of anti-Thy-1-mediated aggregation was further shown by the Thy-1 gene transfection into non-Thy-1 expressing cell lines. Thy-1.1 gene transfected mastocytoma cells were not aggregated by anti-Thy-1.1 antibody.